2018
DOI: 10.1186/s13287-018-0941-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow derived mesenchymal stem cells ameliorate inflammatory response in an in vitro model of familial hemophagocytic lymphohistiocytosis 2

Abstract: BackgroundFamilial hemophagocytic lymphohistiocytosis 2 (FHL2) is the most common familial type of hemophagocytic lymphohistiocytosis with immune dysregulation. FHL2 patients have mutations in the perforin gene which cause overactivation and proliferation of cytotoxic T lymphocytes and natural killer cells. Perforin is the key component of the cytolytic granule response function of cytotoxic T lymphocytes and natural killer cells. Perforin dysfunction causes a cytotoxic immune deficiency with a clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…MSCs have demonstrated promising therapeutic potentials when used in different diseases and in tissue regeneration. They were successfully deployed in the management of neural injuries, GVHD (graft versus host disease), cardiac regeneration, and most importantly autoimmune diseases [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. MSCs display a unique combination of immunoregulatory/immunosuppression, tissue regeneration/repair, and anti-fibrotic properties [59,60] which make them a suitable therapeutic modality for autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have demonstrated promising therapeutic potentials when used in different diseases and in tissue regeneration. They were successfully deployed in the management of neural injuries, GVHD (graft versus host disease), cardiac regeneration, and most importantly autoimmune diseases [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. MSCs display a unique combination of immunoregulatory/immunosuppression, tissue regeneration/repair, and anti-fibrotic properties [59,60] which make them a suitable therapeutic modality for autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs-CM shows promising opportunities for the therapy of various diseases including cancer, inflammation-induced tissue damage, and neurodegenerative diseases [25,26]. It has been shown that factors secreted by MSCs-CM influence cell proliferation, differentiation, immunoregulation, as well as regeneration [22,23,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Human bone marrow-derived MSCs were obtained and characterized as described our previous report in accordance with the Hacettepe University Local Ethical Committee (LUT12/134-16) [22]. Conditioned media of P2 and P3 MSCs were freshly collected and filtered (0.22 μm filters) before use.…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also many studies on the application of CRISPR/Cas9 to construct in vitro cell models of autoimmune diseases. Sevim et al constructed a model for familial hemophagocytic lymphohistiocytosis 2 (FHL2) in order to assess the effectiveness of coculturing with mesenchymal stromal cells as an alternative therapy when bone marrow transplantation is unavailable ( Sevim et al, 2018 ). The autoimmune regulatory gene (AIRE) has also been investigated using CRISPR technology, revealing that disruption of adhesion between the thymic medullary epithelial cells and thymus cells is one mechanism through which AIRE interference leads to autoimmunity ( Speck-Hernandez et al, 2018 ).…”
Section: Crispr/cas9 Application For Autoimmune-related Diseasesmentioning
confidence: 99%